A Taxonomic Search Engine: Federating taxonomic databases using web services - Page Roderic DM (BMC Bioinformatics, 2005)
Abstract Background The taxonomic name of an organism is a key link between different databases that store information on that organism. However, in the absence of a single, comprehensive database of organism names, individual databases lack an easy means of checking the correctness of a name. Furthermore, the same organism may have more than one name, and the same name may apply to more than one organism. Results The Taxonomic Search Engine (TSE) is a web application written in PHP that queries multiple taxonomic databases (ITIS, Index Fungorum, IPNI, NCBI, and uBIO) and summarises the results in a consistent format. It supports "drill-down" queries to retrieve a specific record. The TSE can optionally suggest alternative spellings the user can try. It also acts as a Life Science Identifier (LSID) authority for the source taxonomic databases, providing globally unique identifiers (and associated metadata) for each name. Conclusion The Taxonomic Search Engine is available at http://darwin.zoology.gla.ac.uk/~rpage/portal/ and provides a simple demonstration of the potential of the federated approach to providing access to taxonomic names.